Production of biogas from co-substrates using cow dung, pig dung, and vegetable waste: A case study in Cambodia - Sokna San; Seyla Heng; Vanna Torn; Chivon Choeung; Horchhong Cheng; Seiha Hun; Chanmoly Or (AIMS Energy)
Sustainable waste management and renewable energy are crucial, particularly in Cambodia, where environmental concerns are rising. Organic waste, including cow dung (CD), pig dung (PD), and vegetable waste (VW), offers a promising source for biogas production and clean and renewable energy. However, the efficiency of this biogas production depends on the type of waste and processing conditions. We evaluated the quality, composition, and volume of biogas generated from organic waste, specifically CD, PD, and VW. Three experimental conditions were tested: 10 kg of CD with 10 liters of water, 5 kg of CD mixed with 5 kg of PD and 10 liters of water, and 5 kg of CD mixed with 5 kg of VW and 10 liters of water. As a result, the conversion of pure CD yielded a total volume of biogas up to 0.391 m3, with a methane percentage (CH4) of 69.18%. The CD mixed with PD, which produced only 0.362 m3 of biogas with a CH4 of 65.51%, and CD mixed with VW, which yielded a total biogas volume of only 0.319 m3 with a CH4 of 68.17%. From the result, it can be concluded that the bioconversion of pure CD into biogas was the most efficient compared to the other two conditions.